LABOUR TURNOVER AND SERVICE DELIVERY IN FEDERAL TEACHING HOSPITALS IN SOUTHEAST NIGERIA - Onyema, Chiemeka; Nwakanma, Queency C.; Princewill, Chikere (African Journal of Social and Behavioural Sciences, 2025)
This study investigated labour turnover and service delivery in Federal Teaching Hospitals in Southeast Nigeria. The study specifically examined the relationship between high staff separation rates and declining quality of care; the effect of high turnover intention on waiting times and service accessibility; and how frequent staff changes influence the delivery of emergency services. The study was grounded in Human Capital Theory. A descriptive research design was employed, targeting healthcare professionals, including doctors and nurses, across selected Federal Teaching Hospitals in Southeastern Nigeria. The sample size for the study was 338, with data collected using a structured questionnaire and interviews. Our data were analysed using the Pearson correlation statistical tool. The findings revealed a negative (-0.782) relationship between high labour turnover and healthcare service delivery, with hospitals experiencing higher separation rates reporting lower quality of care, and extended waiting times. Additionally, we found a strong negative correlation (-0.729) between high turnover intention and accessibility of services. The most severe impact was observed in emergency service units, where a strong negative correlation (-0.751) was found between frequent staff changes and the accessibility of emergency services. Limitations of the study include potential response bias from participants and the focus on a specific geographic region, which may affect the generalizability of the findings. Based on the findings of this study, the researchers made the following recommendations: Federal Teaching Hospitals should implement comprehensive employee retention strategies that include competitive remuneration, career advancement programs, improved working conditions, and adequate welfare packages. Teaching hospitals should revise and strengthen their human resource management policies to include structured retention plans, clear career progression paths, and employee recognition programs. Hospitals should also establish regular feedback mechanisms that allow employees to voice their concerns and suggestions, ensuring that their needs are adequately addressed.